Total synthesis: an enabling science - Nay, Bastien (Beilstein journal of organic chemistry, 2023)
Keywords: chemical complexity; natural products; synthetic methodologies; total senthesis Total synthesis is a topic strongly related to synthetic methodology developments and to natural product isolation or biosynthesis. [...]thematic issues dealing with total synthesis in the Beilstein Journal of Organic Chemistry have naturally been published in these fields, such as "Transition-metal and organocatalysis in natural product synthesis" (edited by D. Chen and D. Ma) [1] or "Natural products in synthesis and biosynthesis" (edited twice by J. Dickschat) [2.3]. [...]total syntheses have also been achieved with enzymes, strengthening the links to biology [15]. [...]the recent boom of artificial intelligence, machine learning, and computational chemistry for retrosynthetic analyses and beyond foreshadows a renewed interest in harvesting increasingly complex synthetic strategies for industrial processes. [...]this is not to forget that organic chemistry, which is above all an experimental science, is performed daily by researchers in the laboratory, and some of these lives can be truly inspiring to current and future generations. [...]party material in this article could be subject to other licenses (typically indicated in the credit line), and in this case, users are required to obtain permission from the license holder to reuse the material.